EU funds as a catalyst of change for the Slovak healthcare system? - Jan Fidrmuc; Kristína Gardoňová; Martin Hulényi; Lukáš Sekelský; Veronika Zlaczká (REGION, 2022)
In the programming period 2007-2013, the European Structural and Investment Fund (ESIF) invested exteuro237 million in Slovak hospitals. We investigate whether this injection of additional funds has improved the quality of healthcare in the targeted hospitals. As a measure of quality, we use the readmission rate (ratio of readmissions within 30 days over total hospitalizations) and the mortality rate. Our results show a statistically significant but small effect of ESIF on the readmission rate but not on the mortality rate. We argue that these results suggest that the main problem in Slovak healthcare is low productivity rather than lack of funding.
Keywords: H51; H87; I18; F36; 330; healthcare; public finance; productivity; difference in differences